Longitudinal assessment of NCAA Division I football body composition by season and player age - Wichmann, T. K.; Wolfson, J.; Roelofs, E. J.; Bosch, T. A.; Bach, C. W.; Oliver, J. M.; Carbuhn, A.; Stanforth, P. R.; Dengel, D. R. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to examine longitudinal body composition changes by position, categorized by season and age, using dual X-ray absorptiometry in NCAA Division I football players. Seven hundred nineteen collegiate male football players aged 18-22 years (X¯¯¯age ± SE = 19.4 ± 0.05 years) were examined. Percent body fat (%BF), fat mass (FM), lean mass (LM), total body mass (TM), bone mineral density (BMD), and visceral adipose tissue (VAT) were measured. Players were categorized into position groups of Linemen, Big Skill, Skill, or Special Team. One player scan was used per season (preseason, postseason, and spring season). Analysis of variance and Tukey HSD assessed total and regional differences across age, position groups, and seasons (significance of p < 0.05). Linemen had the greatest FM and LM measures compared with other groups for season and age. From preseason to postseason, %BF, FM, LM, and BMD significantly decreased for each position group. From postseason to spring season, %BF, FM, and VAT decreased, whereas LM increased within each position group. FM, VAT, LM, and TM increased with age in all position groups. The findings of this study indicate that body composition significantly worsened from preseason to postseason and improved from the preseason and postseason to the spring season.